Gendered Pathways to Science: The Perceived Impact of Social Ties and Individual Preferences - Danilo, Estelle; Shi, Youjia; Pflaumer, Gabriela (Columbia Undergraduate Research Journal, 2019)
Despite the huge effort taken to promote gender parity in Science Technology Engineering and Mathematics education, women remain overwhelmingly underrepresented in these fields. Current literature has demonstrated that there are significant processes that influence whether or not someone pursues STEM; yet, none of them specify the perceived individual and environmental factors that correlate with persistence in STEM education. Ergo, the focus of this paper is to try to account for the individual and social causes of persistence in pursuing STEM studies, as perceived by women and men who chose and continued to study STEM at college; more specifically, the nature, timing, and relative influence of these perceived determinants and how they vary according to gender. We have not followed a traditional quantitative research protocol that reaches causal claims. Instead, we have used self-reported retrospective data that offer subjective insight into the perceived determining factors to enter the pathway to STEM at college. To do so, we have conducted a survey, situating STEM undergraduate students at Columbia University in a sequence of events, influences, interactions, and institutions that are successively associated with their current orientation towards STEM disciplines. This research design has enabled us to look at the relative perceived influence of their social ties and individual preferences at three different stages of their life. While men and women who chose to major in STEM do not seem to have fundamentally different perceived individual preferences, they do seem to perceive the contribution of their social environment to their interest in science differently.